Comprehensive audiological assessment system - Kunov, Hans; Madsen, Poul; Sokolov, Yuri; Sokolova, Olena (Canadian Acoustics, 1997)
A new approach to comprehensive audiometry is introduced. This new concept of audiological assessment makes it possible to perform a battery of tests at the same work station during a single visit of the patient. An integrated audiometric instrument, the Audiological Assessment System, is also designed. This system saves clinic space. It is easy and convenient to use due to uniformity and similarity of an operator interface to that in conventional arrangements. Maintenance, service, calibration and upgrading of the system is a one-step process. Thus it is time- and cost-effective. The system enables effective handling of clinical data.